Metabolic variations in normal and fibrotic human laryngotracheal‐derived fibroblasts: A Warburg‐like effect. (1st September 2016) - Ma, Garret; Samad, Idris; Motz, Kevin; Yin, Linda X.; Duvvuri, Madhavi V.; Ding, Dacheng; Namba, Daryan R.; Elisseeff, Jennifer H.; Horton, Maureen R.; Hillel, Alexander T.
Abstract : Objectives/Hypothesis: Laryngotracheal stenosis (LTS) is a chronic fibrotic disease characterized by fibroblast proliferation, collagen deposition, and matrix remodeling in the lamina propria of the larynx and/or trachea. Current medical therapies are limited by a poor understanding of the effector cell's (fibroblasts) cellular biology and metabolism. The purpose of this study was to compare cellular proliferation, function, and metabolism between normal and LTS‐derived fibroblasts in vitro. We hypothesize that LTS‐derived fibroblasts will demonstrate aberrant behavior with faster proliferation, increased collagen production, and altered metabolic allocation compared with normal fibroblasts. Study Design: In vitro comparative analysis. Methods: Human biopsies of normal and iatrogenic LTS tissue (n = 7) were obtained, and fibroblasts were isolated and cultured in vitro. Cellular proliferation, cellular histology, gene expression, and metabolic analyses were performed. Statistical analyses comparing normal and scar‐derived fibroblasts were performed. Results: LTS fibroblast proliferation rate, cellular surface area, and collagen‐1 expression were increased compared to normal fibroblasts. Cellular metabolic analysis of LTS‐derived fibroblasts demonstrated reduced oxidative phosphorylation and increased glycolysis/oxidative phosphorylation ratio compared with normal fibroblasts. Conclusions: Human iatrogenic LTS‐derived fibroblasts demonstrated aberrant behavior when compared with normal fibroblasts. A Warburg‐like effect was revealed, suggesting human iatrogenic LTS fibroblasts drive their proliferation with aerobic glycolysis. The distinct metabolism suggests metabolic inhibitors could reduce fibroblast hyperplasia and hypertrophy in LTS and fibrosis in general. Level of Evidence: NA Laryngoscope, 127:E107–E113, 2017